Clinical bone-conduction standard values for the Bruel and Kjaer 4930 artificial mastoid - Malika Nandur (Journal of All India Institute of Speech and Hearing, 1970)
Calibration of any measuring instrument is a major prerequisite for its use and Audiolog as a scientific discipline respects precision in clinical and research measurements. Accurateaudiometric calibration is crucial in clinical audiology in that the results of audiological evaluations are critical for diagnosis, treatment and rehabilitation of hearing problems